Methodological bases of building the system of key performance indicators for stimulating the project participants in executive bodies - L. A. Zhigun (Russian Journal of Economics and Law)
Objective: the scientific understanding of the individual key performance indicators function within the mechanism of stimulating the participants of project activities of executive authorities is supplemented with knowledge of the direction and impact of their actions.Methods: combination of logical and analytical deduction of theories and methodologies of stimulating the project activity participants under the stimulating influence of key performance indicators at executive authority bodies; identification of correlation dependence of the stimulated participants’ behaviour by the data of questionnaire survey of project activity experts. Results: on the basis of theoretical and methodological provisions and evidence of the stimulating effect of key performance indicators in the activity of project participants, it is proved that the effect has a complex mechanism inherent in project activities of executive authorities. It is determined that the key performance indicators serve as a means of identifying problem areas of the system of project participants’ motivation. The quantitative ratios are found of the stimulating influence of non-material and material individual key performance indicators on the project success, as well as the required working hours and the value-oriented importance of observing them. It is proposed to supplement the individual key performance indicators with an indicator that focuses the project activities towards the project success. The results show that unsystematic adoption of any key performance indicators as the main one leads to a significant deterioration of the stimulating impact of the remaining indicators on the project participants. It is revealed that the activities of the project participants are mostly (26,2 %) focused on the qualitative implementation of the project activities, and to the least degree (14,9 %) - on the observance of discipline. The most time-consuming activity (15,2 %) for the project participants is obtaining unique results. The quantitative rule is found that the maximization of the project complexity stimulation leads to the minimization of the incentives for the qualitative implementation of the project activities and the uniqueness of its results.Scientific novelty: for the first time it is determined that the key performance indicators in their economic form reflect three types of costs: conditionally constant and variable part of payment, as well as transaction costs for the purpose-orientation of the project participants.Practical significance: the main provisions and conclusions of the article can be used in research of the stimulating effect of key performance indicators on the activity of project participants and in the development of methods for building systems of key performance indicators to stimulate them in the executive authority bodies.